PENGARUH KOMPENSASI DAN PEMBERDAYAAN TERHADAP KINERJA MELALUI MEDIASI KEPUASAN KERJA (Studi pada Badan Kesatuan Bangsa dan Politik Provinsi Jawa Tengah) - Surono, Surono; Rozak, Hasan Abdul (Jurnal Ilmiah Telaah Manajemen, 2017)
The study aims to examine, analyzed, and describe the influence of compensation and empowerment against the performance through the medication of job satisfaction on Badan Kesatuan Bangsa dan Politik of central Java Province.Sampling was done by census of all employees on Badan Kesatuan Bangsa dan Politik of Central Java Province totaling 94 (ninty for) respondents. Mechanical testing of the data used in this study include validity, reliability, coefficient determination test, F test, test hypotheses and test the mediating effect.The results showed that, compensation positive and significant impact on job satisfaction, compensation is not a positive influence on performance, empowerment is not a positive influence on performance, and job satisfaction and significant positive effect on performance proven.Job satisfaction mediate in total or in full mediation of compensation to performance while the influence of direct compensation to performance is not significant. Likewise, job satisfaction proved to mediate in total or full mediation of empowerment on performance. While the influence of direct empowerment is also no positive effect on performance. There in the findings interesting, the path analysis model is the best of other model, because produce the biggest. Should be a model this developed efficiency by management, if want to employees in organization it’s improved performance achievements. Key word : compensation, empowerment, job satisfaction, performance